Clinical and Laboratory Findings of Visceral Leishmaniasis in Children Hospitalized in Mashhad, Northeastern Iran: A Twenty-Year Retrospective Study - Seyed Aliakbar SHAMSIAN; Abdolmajid FATA; Reza ALINEZHAD; Mehdi MOHEBALI; Fatemeh SADABADI; Elham MOGHADDAS; Mahdi FAKHAR (Iranian Journal of Parasitology, 2020)
Background: Over the last decade, a few cases of visceral leishmaniasis (VL) have been reported in some provinces of northeastern Iran. We aimed to investigate clinical and laboratory findings of VL among children who admitted to the pediatric ward in a referral hospital in Mashhad, northeastern Iran.